Association between knowledge, attitudes, and practices on food waste and socioeconomic and demographic variables among selected University of the Philippines Diliman undergraduate students - Benabaye, Saul Andrew B.; Mahusay, Niel Matthew B.; Maruji, Kiana Azra J.
Food waste poses a significant challenge in the global fight against hunger and food insecurity. In the Philippines, many citizens are food insecure and malnourished, yet substantial amounts of food are wasted. Young adults abroad, including undergraduate students, are particularly wasteful due to their lack of knowledge on the subject. This study aimed to determine if Filipino undergraduate students exhibit similar behaviors. Using a 2-stage cluster sampling, 147 students from UPD’s College of Engineering were surveyed. The questionnaire, validated through various methods, assessed demographics and food waste-related knowledge, attitudes, practices (KAP) of the respondents. Descriptive analysis revealed that students have moderate knowledge scores, lacking an understanding towards food storage, consumption, and the environmental impacts of food waste. Positive attitudes reflect frugality and a sense of obligation to not waste food. Practice scores were moderate, showing favorable food purchasing practices but counterproductive food-sharing and unfavorable food disposal practices. Profile analysis revealed that sex and income do not significantly influence students' KAP related to food waste. Pearson’s correlation coefficient tests found that while knowledge alone does not strongly influence attitudes or practices, positive attitudes are associated with better practices. Future interventions should consider using the SBCC framework and communication materials that bridge identified knowledge gaps, provide practical ways to save food, and utilize statements that resonate with frugality and obligation to save food, since positive attitudes tend to drive food waste reduction practices more effectively than knowledge alone.